DESAIN DAN UJI COBA LEMBAR KERJA PESERTA DIDIK BERBASIS CTL PADA MATERI LAJU REAKSI: LEMBAR KERJA PESERTA DIDIK BERBASIS CTL - LAZULVA LAZULVA; Nurhafizoh Nurhafizoh (Journal of Research and Education Chemistry, 2022)
This research was instigated by student workbook Contextual Teaching and Learning based that was not yet developed on Reaction Rate lesson. Besides, the students cold not relate what they learnt and how the knowledge should be applied in their daily lives. This research aimed at producing student workbook Contextual Teaching and Learning based on Reaction Rate lesson and knowing the validity and practicality level, and student response to the produced workbook. It was a Research and Development with 4-D (Define, Design, Develop, Disseminate) model. It was administered at State Senior High School 2 Kampar, and the subjects of this research were student workbook media design experts, learning material experts, Chemistry subject teachers, and students. The object was student workbook Contextual Teaching and Learning based on Reaction Rate lesson. The collected data were primary—the data were obtained directly from questionnaire. The instruments of collecting the data were validity test questionnaire, practicality test questionnaire, and student response test questionnaire. The obtained data then were analyzed by using Descriptive qualitative and quantitative analysis techniques. Based on the produced workbook that was tested, its validity level was 88.78% percentage (very valid), its practicality level was 88 % percentage (very practical), and student response was 88 % percentage (very good). Based on these results, it could be concluded that student workbook Contextual Teaching and Learning based was valid and practical on Reaction Rate, so it was appropriate to be an additional teaching material for the teachers at school.